Quantitative Evaluation of the Sarcomere Network of Human hiPSC-Derived Cardiomyocytes Using Single-Molecule Localization Microscopy - Lemcke, Heiko (Int J Mol Sci, 2020)
The maturation of iPSC-derived cardiomyocytes is still a critical point for their application in cardiovascular research as well as for their clinical use. Although multiple differentiation protocols have been established, researchers failed to generate fully mature cardiomyocytes in vitro possessing identical phenotype-related and functional properties as their native adult counterparts. Besides electrophysiological and metabolic changes, the establishment of a well structured sarcomere network is important for the development of a mature cardiac phenotype. Here, we present a super resolution-based approach to quantitatively evaluate the structural maturation of iPSC-derived cardiomyocytes. Fluorescence labelling of the α-actinin cytoskeleton and subsequent visualization by photoactivated localization microscopy allows the acquisition of highly resolved images for measuring sarcomere length and z-disc thickness. Our image analysis revealed that iPSC and neonatal cardiomyocyte share high similarity with respect to their sarcomere organization, however, contraction capacity was inferior in iPSC-derived cardiac cells, indicating an early maturation level. Moreover, we demonstrate that this imaging approach can be used as a tool to monitor cardiomyocyte integrity, helping to optimize iPSC differentiation as well as somatic cell direct-reprogramming strategies.